ADVOCATE: A Legislative Advocacy Model for Counseling Students - Jacquelyn E Schuster; Lauren Rocha; Angie Sevillano; Felicia Green-Johnson; Jennifer Gerlach (Teaching and Supervision in Counseling, 2021)
In the classroom, master’s students learn that advocacy is a central component of the counseling profession and counselor identity, whereas doctoral students train to be advocacy leaders. While counselor educators often infuse advocacy into the classroom through assignments and use current advocacy models present in the literature, we found a need for a practical model specifically for legislative advocacy to implement with counseling graduate students outside of the classroom. The authors pulled from their collective experience of meeting with state legislators at the state Capitol to create the ADVOCATE Model, a practical, step-by-step guide to legislative advocacy. The authors share the details of their model and discuss implications and recommendations for counselor educators and students.
Keywords: advocacy; counselors-in-training; legislative advocacy; counselor education